Metodologías aplicadas a proyectos integrados de yuca: Memorias del congreso latinoamericano celebrado en Villahermosa, México, 26 a 28 de octubre de 1987 - Pérez C., C.A. (International Center for Tropical Agriculture, 1989)
Delegates from Brazil, Colombia, Cuba, Ecuador, Mexico, Nicaragua, Panama, and Paraguay met to examine the systems used in the planning and operation of integrated cassava programs at the national level. Strategies were compared, common elements were defined, and an attempt was made to define an operational methodology to strengthen these programs. It was agreed that their final goal is socioeconomic; they should also cover the entire spectrum of production, transformation, and commercialization of the product. The managerial training of producers should be guaranteed and producer organizations reinforced. To ensure greater possibilities of success, programs should complete a series of successive phases such as macroplanning, establishment of pilot projects, replication of projects in other regions, and commercial expansion of activities. These programs should evolve towards their consolidation in national societies that promote the communication regarding cassava. (CIAT)